(untitled) (Research, Society and Development, 2022)
Hospitals are complex organizations whose functioning requires both technical and administrative activities. The hospital’s raison d’être is to ensure quality in patient care. A viable way to achieve this objective is the correct use of the Lean Healthcare Philosophy, which is derived from the techniques of the Toyota Production System. The present study aims to highlight Lean Healthcare and its characteristics through a conceptual model built from the scientific literature. The study consists of an explanatory and descriptive research with a qualitative approach. In addition, bibliographic research was used to support the article. The results indicate that the success of Lean Healthcare is strongly associated with the participation of people, the creation of an organizational culture focused on continuous improvement. In addition, the correct use of Lean tools was also seen as a conditioning factor for the success in the practice of this philosophy. These situations, together with the employees’ attitudes towards continuous improvement, represent the necessary inputs for the Lean Healthcare process to work properly. Depending on the conceptual model proposed, this will lead to the improvement of hospital processes, the finding of pertinent solutions to the hospital’s problems, the creation of value for patients in each task performed and the productive use of resources. Thus, the results generated in this perspective are the reduction of waste, the improvement in the services provided, the reduction of costs and, therefore, the increase in the hospital’s results.